Konseling Islam melalui Literasi Ayat Al-Qur'an untuk Mengatasi Self-Injury: Studi Kasus Klien 'M' - Yeyen Putri Anggraini; Abdur Razzaq (Scidacplus, 2025)
Self-injury, or non-suicidal self-injury (NSSI), is the deliberate act of harming one's own body without suicidal intent, typically performed to relieve overwhelming emotional distress. National survey data indicate that self-injurious behavior remains prevalent among Indonesian youth, underscoring the urgency of culturally grounded interventions. This study examines how Islamic counseling through literacy of Qur'anic verses can be used to address self-injury in client M, a young woman who engaged in repeated self-harming behaviors such as cutting, head-banging, and hair-pulling. The study aims to (1) describe the pattern of self-injury exhibited by client 'M' and (2) examine how Islamic counseling through Qur'anic literacy contributed to reducing this behavior. A qualitative case study design was employed, following Yin's approach to single-case research. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using pattern matching, explanation building, and time-series analysis, with triangulation used to strengthen data trustworthiness. The intervention consisted of five structured counseling sessions in which the client was guided to read, comprehend, and internalize (tadabbur) selected Qur'anic verses related to self-preservation and patience (sabr). The findings show that client 'M' exhibited several indicators consistent with established NSSI typologies, including difficulty regulating emotion, low self-esteem, rigid thinking patterns, and fear of change. Following the five counseling sessions, the client demonstrated a shift toward more positive affect, a greater sense of religious meaning, increased self-awareness regarding the religious prohibition against self-harm, and a stated commitment to reducing self-injurious behavior. These outcomes are consistent with prior research suggesting that Qur'an-based spiritual interventions can support emotion regulation and reduce psychological distress. The study suggests that Islamic counseling rooted in Qur'anic literacy offers a culturally and spiritually congruent complement to conventional self-injury interventions, particularly for Muslim clients.